Báo cáo tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với dự thảo Luật Thanh tra (sửa đổi) (Số: 2329 /BC- TTCP) - Thanh tra Chính phủ (2021)
Toàn văn Báo cáo tiếp thu, giải trình ý kiến thẩm định của Bộ Tư pháp đối với dự thảo Luật Thanh tra (sửa đổi) (Số: 2329 /BC- TTCP)